The impact of capital enrichment on total factor productivity from the perspective of innovation capability - Lina Ma; Fengju Xu; Najaf Iqbal (Journal of Applied Economics, 2022)
Innovation capability of manufacturing industry is one of the most important factors that determine a country's competitiveness. This paper expounds the theoretical and empirical relationship among innovation capability (IC), capital enrichment (CE) and total factor productivity (TFP) by using the yearly panel data of 28 Chinese manufacturing segments from 2011 to 2018. The intermediary effect model and threshold model are used for empirical analysis, findings suggest that 1) IC not only directly promotes TFP but also indirectly through CE, indicating that CE has an intermediary effect on the relationship between IC and TFP. 2) The positive effect of CE on TFP is influenced by the "double threshold effect" of IC. Compared with industries having low IC, this positive effect in high IC industries is first enhanced then weakened and later re-enhanced. 3) There is a significant difference in IC and CE among different manufacturing segments.
Keywords: 330; capital enrichment; double threshold effect; Innovation capability; intermediary effect; total factor productivity